Does Privatisation Contribute to the Performance of a Health Care System?. (June 2014) - Zweifel, Peter
Abstract This paper considers whether privatisation can contribute to the performance of a health care system. In order to answer this question, five well‐known criteria of economic performance are proposed. The finding is that privatisation is quite likely to contribute to all of these criteria. The crucial condition, however, is that privatisation does not amount to the creation of public monopolies.